Knowledge and power : the information theory of capitalism - Gilder, George (Washington, DC : Regnery Gateway, 2022)
One of the twentieth century's defining economic minds proposes a new theory on how capitalism produces wealth and how the American economy can regain its vitality and growth.
Includes bibliographic references and index.
Keywords: Information theory in economics -- United States; Entrepreneurship